VOSTOK - the Voxel Octree Solar Toolkit - Bechtold, Sebastian; Höfle, Bernhard (Universität, 2020)
VOSTOK is a command-line tool to compute a detailed model of incoming solar radiation distribution on a patch of land, including structures like buildings and vegetation, represented by a 3D point cloud data set. The program is written in C++ and makes use of the "SOLPOS.H" library ( http://rredc.nrel.gov/solar/codesandalgorithms/solpos/) to compute the angular position of the sun in the sky for a given location on Earth and a given moment in time. VOSTOK can use any 3D point cloud (e.g. LIDAR, SfM) as XYZ-locations (with surface normal vector information) for which the incoming sunlight shall be computed (the computation points)